2020
DOI: 10.1177/0194599820951166
|View full text |Cite
|
Sign up to set email alerts
|

Pass/Fail Scoring of USMLE Step 1 and the Need for Residency Selection Reform

Abstract: The Federation of State Medical Boards and the National Board of Medical Examiners recently announced a change in the United States Medical Licensing Examination Step 1 scoring convention to take effect, at the earliest, on January 1, 2022. There are many reasons for this change, including decreasing medical student stress and incentivizing students to learn freely without solely focusing on Step 1 performance. The question remains how this will affect the future of the otolaryngology–head and neck surgery mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 10 publications
1
27
0
1
Order By: Relevance
“…Higher USMLE scores increase applicants’ chances of matching 6,9 and are valued by program directors. 8 While higher USMLE Step 1 scores increase the odds of matching in OTO-HNS by 2.6 times, the effect was not significant. Hauser et al 6 found step 1 scores significantly impact matching odds using 2009 to 2013 data.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Higher USMLE scores increase applicants’ chances of matching 6,9 and are valued by program directors. 8 While higher USMLE Step 1 scores increase the odds of matching in OTO-HNS by 2.6 times, the effect was not significant. Hauser et al 6 found step 1 scores significantly impact matching odds using 2009 to 2013 data.…”
Section: Discussionmentioning
confidence: 94%
“…With the upcoming change in step 1 scoring (described below), step 2 may carry even greater importance moving forward. 8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research is warranted to better understand the influence of clerkship grading scheme on match outcomes. Finally, it is unknown how the findings from this study will be influenced by new changes to the residency selection process such as the transition of USMLE Step 1 to Pass/Fail 17 and the implementation of preference signaling in otolaryngology 18 …”
Section: Discussionmentioning
confidence: 99%
“…1,6 Moreover, as more than half of OTO-HNS programs use USMLE scores as a screening tool, 41 the recently announced change of the USMLE Step 1 examination to pass/fail scoring furthers the need for residency selection reform. 69,70 Additional reasons supporting the need for process reform include curtailing the massive application cycle costs incurred by applicants, 3,37 increasing the understanding of which applicant characteristics are best correlated with an ideal resident, 8 and ultimately ensuring the highest quality of future otolaryngologists to lead the specialty.…”
Section: The Need For Residency Selection Reformmentioning
confidence: 99%